The Influence of Green Innovation, Green Market Orientation, and Marketing Capabilities on The Marketing Performance of Green MSMEs - Qomariyah, Diyah Rahayu Nur; Nuvriasari, Audita (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the effect of Green Innovation, Green Market Orientation, and Marketing Capability on the marketing performance of Green MSMEs in Yogyakarta. The sample in this study was 96 owners or managers of green MSMEs using the purposive random sampling technique through a questionnaire. The results of the Instrument Test state that the data in this study are proving to be valid and reliable. The results of the Classical Assumption Test stated that the data in this study were normally distributeid and produced a regression model that was free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) Green Innovation has a negative and significant effect on the Marketing Performance of Green MSMEs in Yogyakarta. (2) Green Market Orientation has a positivei and significant effect on the Marketing Performance of Green MSMEs in Yogyakarta. (3) Marketing Capability has a positive and significant effect on the Marketing Performance of Green MSMEs in Yogyakarta.